[tex]f(x) =4 x {}^{3} - 4x {}^{2} - 16x + 16[/tex]
[tex]divide \: by \: x - 2[/tex]
[tex]4x {}^{2} \: into \: (x - 2) = 4x {}^{3} - 8x {}^{2} [/tex]
[tex]g(x) = 4x {}^{2} - 16x + 16[/tex]
[tex]4x \: into \: (x - 2) = 4x {}^{2} - 8x[/tex]
[tex]z(x) = - 8x + 16[/tex]
[tex] - 8 \: into \: (x - 2) = - 8x + 16 \\ no \: remainder[/tex]
[tex]f(x) = (x - 2)(4x {}^{2} + 4x - 8)[/tex]
[tex]f(x) = 0 \\ x - 2 = 0 \: \: \: \: \: \: \: \: \: 4x {}^{2} + 4x - 8 = 0 \\ [/tex]
[tex]x = \frac{ - 4 + \sqrt{4 {}^{2} - 4(4)( - 8) } }{2(4)} = \frac{ - 4 + \sqrt{144} }{8} = \frac{ - 4 + 12}{8} = 1[/tex]
[tex]x = 2[/tex]
[tex]x = \frac{ - 4 - 12}{8} = \frac{ - 16}{8} = - 2[/tex]